Managerial activity of the future specialists of higher mia educational institutions of Ukraine as a subject of research - Троцький, Руслан Сергійович (ScienceRise: Pedagogical Education, 2016)
The essence of the notion “managerial activity of the future specialists of higher MIA educational institutions of Ukraine” was analyzed; the specificity of managerial activity was elucidated through the prism of ideas of the theory of management, psychology of management, theory of general pedagogy. It was generalized, that the basic principles of Ukrainian legislation determine the priorities of the law enforcement bodies reformation taking into account the specificity of management system and prospects of formation of contingent of the officers of the law that must be able to realize the professional activity at the high professional level. On the base of analysis of psychological-pedagogical literature it was elucidated, that determination of the new functions of managerial activity makes possible its social efficiency, development of managerial culture, readiness to the managerial activity, managerial qualities of students. It was determined, that being grounded on functional differentiation, managerial activity provides the precise realization of professional tasks, economy, regularity, rhythmicity, reliability of the work, exclusion of mistakes and disorders in joint activity, creation of conditions for initiative and creative activity, ensuring psychological support for self-development and self-improvement of leader, other specialists, validity of prospective aims of organization activity, management of human resources, setting of professional communication